p.G12C KRAS mutation prevalence in non-small cell lung cancer: Contribution from interregional variability and population substructures among Hispanics (2022)
Antecedentes: El exón 2 de KRAS p. La mutación G12C en pacientes con adenocarcinoma de pulmón ha ido aumentando en relevancia debido al desarrollo y la eficacia de nuevos medicamentos de tratamiento. Estudios en diferentes poblaciones indican que la variabilidad regional entre etnias y ascendencias podría desempeñar un papel fundamental en el desarrollo de esta alteración molecular dentro del cáncer de pulmón. Results: Included were 979 patients with a national mean frequency for the KRAS exon 2 p.G12C mutation of 7.97% (95%CI 6.27-9.66%). Variation between regions was also identified with Antioquia reaching a positivity value of 12.7% (95%CI 9.1-16.3%) in contrast to other regions such as Bogota DC (Capital region) with 5.4% (2.7-8.2%) and Bolivar with 2.4% (95%CI 0-7.2%) (p-value = 0.00262). Furthermore, Short tandem repeat population substructures were found for eight markers that strongly yielded association with KRAS exon 2 p.G12C frequency reaching an adjusted R2 of 0.945 and a p-value of < 0.0001. Conclusions: Widespread identification of KRAS exon 2 p.G12C mutations, especially in cases where NGS is not easily achieved is feasible at a population based level that can characterize regional and national patterns of mutation status. Furthermore, this type of mutation prevalence follows a population substructure pattern that can be easily determined by population and ancestral markers such as STR.